Классификация и клинические особенности хронических гнойных средних отитов - Гусаков, О. Д.; Гусакова, О. О.; Gusakov, А. D.; Gusakova, А. А.; Гусакова, Олександра Олександрівна (My University, 2019)
В лекции систематизированы сведения об этиологии, патогенезе, клиническом течении хронического воспаления среднего уха. Авторы акцентируют внимание на характере проявлений отита в зависимости от размера и места расположения перфорации барабанной перепонки. Исходя из личного опыта и накопленных знаний, детально раскрывают вопрос холестеатомы, ее предвестников и возможных осложнений. Немало внимания уделяется методам обследования и интерпретации аудиометрических и рентгенологических данных контроля. Говоря о хроническом течении заболевания уха, в статье описаны часто встречающиеся ситуации, такие как тимпаносклероз, фистула лабиринта и др. Помимо собственной точки зрения на проблему, авторы представляют литературные данные, отображающие воззрения других оториноларингологов. In this lecture information on the etiology, pathogenesis, and clinical course of chronic inflammation of the middle ear is systematized. The authors focus on the nature of the manifestations of otitis media, depending on the size and location of the perforation of the eardrum. Based on personal experience and accumulated knowledge, in detail reveal the issue of cholesteatoma, its precursors and possible complications. A lot of attention is paid to methods of examination and interpretation of audiometric and radiological control data. Speaking about the chronic course of the ear disease, the article describes frequently encountered situations such as tympanosclerosis, fistula, etc. In addition to their own point of view on the problem, the authors present literature data reflecting the views of other otorhinolaryngologists.
Classification and clinical features of chronic purulent otitis media
Keywords: хронический отит; тугоухость; холестеатома; ретракционный карман; тимпаносклероз; chronic otitis; hearing loss; cholesteatoma; retraction pocket; tympanosclerosis